Análisis comparativo técnico-económico de muros de suelo reforzado con geotextiles con otras alternativas equivalentes. - Hernández-Astorga, Fernando (Instituto Tecnológico de Costa Rica., 2011)
According to the new requirements demanded by the labor market in the construction of infrastructure projects, this because every day the problems of slope stability in our country are becoming more evident because the company has had to resort to land with slopes greater to build paid to the heavy rainfall that hit our country in times of winter, which is why there is a need for an analysis of the effects that moisture has on the ground, this moisture characteristics directly influences the soil, which may be responsible for the failures that may occur.
Proyecto de graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2011.
Keywords: Probabilidad; Precipitaciones; Costos; Experimentos de laboratorio; Materiales de relleno